Review of Integrated Response Timing in Post-Monitoring Complex Dangerous Cargo - Maruf Misaal; Lai Fatt Chuah; Mokhtar Kasypi; Anuar Abu Bakar; Mohd Azhafiz Abdullah; Shahrul Miza Mahmud; Keng Bin Loke; Wan Mariam Wan Abdullah; Mohammad Tameem Hossain Azmi; Ehamadul Haque Ani (Chemical Engineering Transactions)
In an interconnected world dominated by global trade and intricate supply chain management, the transportation and management of dangerous cargo such as flammable liquids, toxic chemicals and radioactive materials, present multifaceted challenges. These hazardous substances pose significant environmental and health risks, necessitating rigorous safety measures and regulatory oversight. This comprehensive overview examines the various types of dangerous cargo, their environmental implications and notable case studies, highlighting the critical importance of international cooperation and stringent regulations. It delves into the regulatory frameworks governing the transport of hazardous materials by rail, sea, air and land, emphasizing the pivotal role of institutions like the International Maritime Dangerous Goods Code and the Environmental Protection Agency. Analysis indicates a need for improved response times in monitoring programs, necessitating adaptability to diverse environments and specific circumstances. Monitoring and impact assessment programs within emergency response frameworks differ from those aimed at detecting long-term trends in physical, biological and chemical variables.